Determination of treatment options for Class III malocclusions in adult patients based on cephalometric values: A systematic review - Sivarajan, Saritha (Sciendo, 2022)
Objective The present systematic review aimed to determine cephalometric values that may be used as a guide in deciding between orthodontic camouflage and orthognathic surgery to treat a Class III malocclusion in adults. In addition, a secondary aim was to identify treatment complications and aesthetic perceptions by laypersons/orthodontists. Methods Without a language restriction, an electronic search of six databases and a hand search of three orthodontic journals were performed until September 2021. All studies comparing orthodontic camouflage and orthognathic surgery in Class III malocclusion patients, were included. Data extraction was carried out independently by two authors with disagreement resolved by a third author. The risk of bias related to individual studies was appraised using a modified version of the STROBE checklist. The results were summarised qualitatively, and no meta-analysis was undertaken due to the high heterogeneity between the studies. Results With the quality of evidence ranging from moderate to high, six retrospective studies were included. A cephalometric analysis comprising the Holdaway angle, overjet, the Wits appraisal, lower incisor inclination, the maxillary-mandibular ratio, overbite, gonial angle and an additional combination were used as a guide. No treatment complications were reported. One study examined the perception of facial profile attractiveness in borderline surgical Class III malocclusions and found no difference in outcome and significant improvements in both camouflage and surgical groups. Conclusion The existing evidence is insufficient to identify a cephalometric parameter threshold in deciding between orthodontic camouflage and orthognathic surgery. PROSPERO database protocol no. CRD42020165164.